PERTUMBUHAN STEK ANGGUR (Vitis vinifera L.) PADA BERBAGAI KONSENTRASI ZAT PENGATUR TUMBUH DAN MEDIA TANAM - Samsul Hidayat; Nuraeni Nuraeni; Syamsiar Syamsiar (Fakultas Pertanian, Universitas Tadulako, 2022)
The purpose of this study was to determine the appropriate concentrations of growth regulators and better growing media for the growth of grape cuttings. It was conducted in Jaya Makmul village, Nuhon sub district of Banggai district. This study used a two-factorial randomized block design. The first was the concentrations of the growth regulator (no growth regulator, 10% growth regulator, 20% growth regulator, and 30% growth regulator) and the second was the planting media (a mixture soil and sand, and a mixture of soil, sand and chicken manure). There were eight treatment combinations, and each treatment was repeated four times to produce 32 experimental units. The results showed that there was an interaction effect between growth regulator and planting media observed on growth rate of shoots of 11.75 days, number of shoots of 2.00, and cutting emergence rate of 66.67%. The mixture of soil, sand and poultry manure in a ratio of 2: 1: 1 showed a highly significant effect on shoot growth rate, number of leaves, leaf area, number of shoots, shoot length and cutting growth percentage. The optimal concentration of growth regulator for grape cuttings was 30% growth regulator concentration.